Ecology of the lichen Cladonia botrytes in Sweden - Bogomazova, Kristine (SLU/Dept. of Ecology, 2012)
ABSTRACT Rapid changes in the forest structure due to logging strongly affect lichen vegetation and can exceed tolerance of many organisms while being beneficial to others. Cladonia botrytes was supposed to be obligately lignicolous and having a high portion of the occurrences on stumps on clear-cuts. The aim of this study was therefore to clarify the ecology of Cladonia botrytes and especially how frequently it occurs on soil in clear-cuts. Scots pine Pinus sylvestris clear-cuts aged 10-12 years old were examined for the abundance of the species on stumps and exposed soil in three provinces of Sweden – Uppland, Dalarna and Västerbotten. C. botrytes was present on the soil in all the regions on two distinct substrates: humus on the ground and on boulders. There was a significant regional difference in the distribution of the lichen on the ground and on boulders (p< 0.001), indicating a trend of increasing abundance towards the north. Regional variation for the occurrence of the lichen on the stumps was significant (p < 0.001); however the distribution among the regions was more homogenous and did not have a distinct northward trend. Canopy cover of the new tree generation influenced the abundance of the lichen on all the substrates: ground, boulders and stumps. It was found that the species prefer dry conditions as it was less abundant in the plots with wet habitats. As for the occurrences on the stumps, it was found that stump size variables (height and surface area) have an effect on the presence of the lichen yet the relationship behind that is unknown. The species is positively affected by the logging activities as it provides short-term habitat. Due to the abundant presence of the lichen on soil, change in the classification as obligatory lignicolous should be considered.